(3Jbjje GdCOGA GdeGdj hOQGSGJ GdLOhis - (3YHO GdZaGQ(B, (3Mfajs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2005)
(3GdJMdjd GdeGdj hGJNGP GdbQGQGJ, GdJMdjd GdeGdj, GdJNWjW GdQCSeGdj hGdQbGHI, SjGSGJ JhRjY GdCQHGM, GdGSJKeGQGJ GdQCSeGdjI, GdGfaGb GdQCSeGdj, CSGdjH Jbjje GdGbJQGMGJ GdGSJKeGQjI aj XQha GdKHGJ hGdJCcO, GdeaGVdI Hjf GdGbJQGMGJ GdGSJKeGQjI GdJj JCcO aj GdMSGH, JcdaI GdCehGd hGJNGP bQGQGJ GdGSJKeGQ, GdJehjd GdOGNdj hGdNGQLj hefgL bjGS JcdaJg, GdGSJKeGQGJ GdOGNdjI(B.s
(3GdeQGLY U(B.421s
Keywords: (3GdGSJKeGQGJ(B- (3QDhS GdCehGds; (3GdJMdjd GdeGdjs; (3GdJNWjW GdeGdjs; (3GdSjGSI GdeGdjIs